2021
DOI: 10.1080/13880209.2021.1961822
|View full text |Cite
|
Sign up to set email alerts
|

SIRT 3 was involved in Lycium barbarum seed oil protection testis from oxidative stress: in vitro and in vivo analyses

Abstract: Context Lycium barbarum L. (Solanaceae) seed oil (LBSO) exerts LBSO exerts protective effects in the testis in vivo and in vitro via upregulating SIRT3. Objective This study evaluates the effects and mechanism of LBSO in the d -galactose ( d -gal)-induced ageing testis. Materials and methods Male Sprague Dawley (SD) rats … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 58 publications
1
5
0
Order By: Relevance
“…Furthermore, expression of was accelerated by melatonin therapy in reactive to PM2.5 exposure, but SIRT1 was not. The obtained results were consistent with those studied by Yang et al, 39 who reported that melatonin could increase the SIRT3 expression in testicular cells, manifesting a probable functional interaction between SIRT3 and melatonin in PM2.5-caused apoptosis. Then, to ascertain whether SIRT3 played a crucial part in mediating the observed protective action of melatonin after PM2.5 exposure, GC-2 cells were pretreated with 3-TYP, the specifical inhibitor of SIRT3.…”
Section: Resultssupporting
confidence: 92%
“…Furthermore, expression of was accelerated by melatonin therapy in reactive to PM2.5 exposure, but SIRT1 was not. The obtained results were consistent with those studied by Yang et al, 39 who reported that melatonin could increase the SIRT3 expression in testicular cells, manifesting a probable functional interaction between SIRT3 and melatonin in PM2.5-caused apoptosis. Then, to ascertain whether SIRT3 played a crucial part in mediating the observed protective action of melatonin after PM2.5 exposure, GC-2 cells were pretreated with 3-TYP, the specifical inhibitor of SIRT3.…”
Section: Resultssupporting
confidence: 92%
“…Moreover, following the treatment with the inhibitors of AMPK (compound C) and SIRT3 (3-TYP), there was an antagonism effect on Curcumin, and the TJ proteins (namely, ZO-1, Occludin, and Claudin-11) in D-gal-treated SCs presented lowered expressions. Intriguingly, SIRT3 was discovered to activate AMPK in several disease models, according to previous studies [45][46][47]. Moreover, it has been reported that Lycium barbarum seed oil stimulates testosterone secretion and reduces oxidative stress partly via the activation of the SIRT3/AMPK signaling pathway in subacutely aging murine testes, and SIRT3 silently decreases the AMPK phosphorylation in TM4 cells [47].…”
Section: Discussionmentioning
confidence: 97%
“…Intriguingly, SIRT3 was discovered to activate AMPK in several disease models, according to previous studies [45][46][47]. Moreover, it has been reported that Lycium barbarum seed oil stimulates testosterone secretion and reduces oxidative stress partly via the activation of the SIRT3/AMPK signaling pathway in subacutely aging murine testes, and SIRT3 silently decreases the AMPK phosphorylation in TM4 cells [47]. Nonetheless, there is growing evidence that AMPK has a regulatory effect on SIRT3.…”
Section: Discussionmentioning
confidence: 99%
“…Antioxidant effect in mitochondria, vascular protection [6,30] 3.1. NF-κB Signal Transduction Pathway NF-κB is a class of nuclear transcription factors that play a significant role in regulating the expression of genes.…”
Section: Alkaloidsmentioning
confidence: 99%